Phishing website detection using genetic algorithm-based feature selection and parameter hypertuning - Silva, Ana Sofia Pulquério (2023)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Business Analytics